2000
DOI: 10.4319/lo.2000.45.3.0703
|View full text |Cite
|
Sign up to set email alerts
|

Climatic factors in the Atlantic control the oceanographic and ecological changes in the Baltic Sea

Abstract: Salinity changes in the Baltic Sea have been attributed to a lack of balance between irregular pulses of North Sea water penetrating the Danish Straits and the freshwater runoff to the Baltic Sea. Both pulses and runoff are controlled by climatic factors in the Atlantic. The occurrence of major pulses of oceanic water has proved unpredictable, being non‐existent during the 1980s. We used dynamic regression models to relate the response of the Baltic Sea salinity to hypothetical controlling factors: westerly wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(133 citation statements)
references
References 19 publications
5
127
0
1
Order By: Relevance
“…It is possible that various chemicals of municipal, industrial, or agricultural origin are involved in the formation of gonad abnormalities in the Baltic herring, and some of them could be related to the changes of the Baltic ecosystem and develop in one way or another as a response to declining salinity that has taken place during the past 30 years (Hänninen et al 2000;. Salinity may affect the hormonal system and reproduction of fish (Billard et al 1981), but most likely a euryhaline species like the Baltic herring is able to adjust to variation of salinity, which is a typical feature of the Baltic Sea.…”
Section: Possible Causes Of Gonad Malformationsmentioning
confidence: 99%
“…It is possible that various chemicals of municipal, industrial, or agricultural origin are involved in the formation of gonad abnormalities in the Baltic herring, and some of them could be related to the changes of the Baltic ecosystem and develop in one way or another as a response to declining salinity that has taken place during the past 30 years (Hänninen et al 2000;. Salinity may affect the hormonal system and reproduction of fish (Billard et al 1981), but most likely a euryhaline species like the Baltic herring is able to adjust to variation of salinity, which is a typical feature of the Baltic Sea.…”
Section: Possible Causes Of Gonad Malformationsmentioning
confidence: 99%
“…We also investigated the annual average temperatures against the NAO indices ( Fig. 3) (Hänninen et al, 2000;Osborn, 2004Osborn, , 2006Osborn, , 2011 and found that on average, lower temperatures are connected to highest negative NAO values, and vice versa (visible also in the 5-year running mean shown in Figs. 2 and 3) (Lehmann et al, 2011).…”
Section: Long-term Changes In Atmospheric Temperaturesmentioning
confidence: 99%
“…Kau Bay) or the North Atlantic Oscillation (e.g. Baltic Sea) (Hanninen et al, 2000;). Advection of North Sea water into the Baltic Sea anoxic basins results in a cascade of biogeochemical reactions with major consequences for food web structure and ecosystem functioning.…”
Section: Hypoxia In Semi-enclosed Seas and Basinsmentioning
confidence: 99%